FEASIBILITY OF SMART SPEAKER USE TO SUPPORT AGING IN PLACE. (11th November 2018) - Choi, Y; Demiris, G; Thompson, H
Abstract: Voice-operated smart speakers may be an effective tool to support healthy aging and wellness of older adults. A smart speaker primarily designed for usage in a home (e.g. Amazon's Alexa®) executes a user's voice commands through an integrated digital personal assistant powered by artificial intelligence. This study explored older adults' attitudes, needs, challenges, and preferences of using commercially available smart speakers to assist in maintaining their independence at home. As part of a larger Internet of Things feasibility study, nineteen older adult participants (65+) chose to have a smart speaker installed in their home for a 2-month deployment study. We conducted three semi-structured interview sessions, one at baseline, one at 1 month, and another at exit to gather participant perspectives pertaining to overall obtrusiveness, needs and preferences and overall attitudes towards this technology. During the exit interview, older adults were asked what kind of improvements or features they would want to have in the future based on their experience with the smart speaker technology. Interview sessions were audio-recorded and transcribed. We conducted a content analysis of these transcripts to identify themes pertaining to participants' perceptions of smart speakers. In general, participants expressed a positive experience with hands-free voice interactions with the smart speaker. The two most frequently used features were 1) asking practical questions (e.g. weather) and 2) managing tasks such as setting a reminder to take medication. Participants discussed its potential to be used as a health management device to keep track of their blood pressure or blood sugar.